Contributing Factors of Anxiety on Healthcare Workers during COVID-19 Pandemic at Referral Hospital of Sumatra Region in Indonesia - Simanjuntak, Christine Raphaela Tiarmauli; Sinaga, Bintang Yinke Magdalena; Siagian, Parluhutan; Effendy, Elmeida; Zaluchu, Fotarisman (Public Health of Indonesia, 2025)
Background:During the Coronavirus Disease 2019 (COVID-19) pandemic, nurses and doctors served as the frontline healthcare workers. Consequently, mental health issues among healthcare workers can develop into significant health problems and impose a substantial social burden, particularly on nurses and doctors working in hospital settings. Objective:To analyze the prevalence and factors influencing anxiety levels among healthcare workers, specifically nurses and doctors, at Adam Malik General Hospital Medan during the COVID-19 pandemic. Methods:This study employed a cross-sectional design with bivariate analysis. Data were collected using the DASS-42 questionnaire, which was distributed to 114 participants comprising nurses and doctors working in both the COVID-19 emergency isolation and ward isolation units. Results:The findings revealed that 29 participants (25.4%) exhibited symptoms of anxiety, with the majority experiencing mild anxiety (13.2%). The nursing profession demonstrated the highest prevalence of anxiety disorders, with 33.3% of nurses reporting symptoms. Being a nurse was significantly associated with higher anxiety levels compared to being a doctor, and working in the emergency isolation room was significantly associated with higher anxiety levels compared to working in the isolation ward or both units (p<0.05). Conclusion:Factors such as gender, marital status, parental status, post-COVID-19 status, family history of COVID-19, vaccination history, and comorbidities did not significantly affect anxiety levels among healthcare workers during the COVID-19 pandemic at Adam Malik General Hospital Medan. However, anxiety was prevalent among healthcare workers, with nurses and those working in the emergency isolation room being particularly affected. Keywords:anxiety; COVID-19; healthcare workers; mental health; Indonesia